Papilomatose laríngea: Análise morfológica pela microscopia de luz e eletrônica do HPV-6 - Martins, Regina Helena Garcia [UNESP]; Dias, Norimar H. [UNESP]; Gregório, Elisa Aparecida [UNESP]; Marques, Mariângela Alencar [UNESP]; Da Silva, Márcia Guimarães [UNESP]; Candeias, João Manuel Grisi [UNESP] (Elsevier, 2008)
Laryngeal papillomatosis is the most frequent benign neoplasia in children. It is caused by HPV 6 and 11. The lesions are exophytic and highly recurrent, compromising the airway mucosa, mainly the larynx. Study design - clinical prospective. Aims: to show morphologic alterations of the epithelium (light and electron microscopy) in the HPV-6 lesions. Methods: specimens of laryngeal lesions obtained during surgery of four children (1 male, 3 female) were submitted to HPV typing (PCR), light microscopy and electron microscopy. Results: in all specimens, HPV type 6 was found. Epithelial projections were found by electron microscopy with superficial cells in desquamation. Light microscopy showed exophytic projections of the keratinized stratified squamous epithelium overlying a fibrovascular core. Koilocytes (vacuolated cells), suggesting the viral infection by HPV, were identified. No alterations were seen in the basement membrane and corion. Ultraestrutural analysis showed vacuolated cells with clear cytoplasmic inclusions, intercellular injuries and widening intercellular spaces. Conclusions: morphologic alterations of the epithelium in the HPV-6 lesions are superficial, and additional studies including the others HPV types are needed to show the more aggressive and extensive aspect of the disease. © Revista Brasileira de Otorrinolaringologia. All Rights reserved.
Laryngeal papillomatosis: Morphological study by light and electron microscopy of the HPV-6
Keywords: Larynx; Microscopy; Papillomatosis; Ultrastructure